The Use of Virtual Reality Platforms in Teaching Artistic Disciplines as a Factor in Creative Development - Al Hussaini, Muzamil Hussain; Abbas, Naveed (The Indonesian Institute of Science and Technology Research, 2025)
This research study investigates the impact of virtual reality (VR) platforms on students' creative development and motivation in artistic education. Employing a mixed-methods research design, 60 undergraduate art students, aged between 18 and 22, were divided into control and experimental groups. Group A received traditional instruction, while Group B engaged with immersive VR tools over six weeks, completing parallel artistic tasks. Creativity levels were measured using the Torrance Tests of Creative Thinking (TTCT), alongside validated motivation questionnaires. Pre- and post-test results revealed a statistically significant improvement in both creativity scores and engagement levels among participants in the VR group compared to the control group (p < .05). Additionally, ANOVA results confirmed the effectiveness of VR-based instruction in enhancing originality, expressive thinking, and creative amplification. The study followed strict ethical protocols, including informed consent and data privacy protection. Findings support integrating VR technologies as pedagogical tools in art education, suggesting that immersive environments foster higher-order thinking and sustained creative focus. Although limited by sample size and study duration, this research contributes to the growing body of evidence advocating digital innovation and creativity in education. Future studies are recommended to examine long-term effects, platform-specific outcomes, and cross-disciplinary applications of VR in creative learning environments.